Structural Optimization-Based Enhancement of the Dynamic Performance for Horizontal Axis Wind Turbine Blade - Ahmed Zarzoor; Alaa Jaber; Ahmed Shandookh (Journal of Applied and Computational Mechanics)
Wind energy is simple and environmentally friendly, it takes the energy of the wind to produce electricity. Wind turbines that have rotor blades connected to generators can efficiently harvest this energy from the wind's motion. The optimization of wind turbine blades is crucial to the success of wind energy technology, beyond the simple mechanical advantage, the pursuit of structural enhancements that have a significant impact on dynamic performance is also involved. This research aims to improve the efficiency and power of wind turbine blades in order to enhance the efficiency and power of the devices. It employs a complex optimization framework that combines aerodynamics and structural analysis via MATLAB and a genetic algorithm. The investigation maximizes the length of the chord, the angle of twist, and the selection of airfoils while maintaining constraints. This work investigates various geometric variables and employs numerical calculations on top of high-performance computing with ANSYS Fluent and ANSYS Structural. The results show significant enhancements in blade performance near the root, which supports the framework's legitimacy. The investigation also focuses on the necessity of estimating torque and the frequency of blade modes in order to reduce the cost of maintenance and ensure operational reliability. This research demonstrates the transformative power of wind turbine blade optimization, it promotes innovation and sustainability in the field of clean energy by achieving 50% improvement in aerodynamic performance and 14% improvement in the modal frequency of the blade while maintaining the weight of the blade.